Sikhs in England : the development of a migrant community - Helweg, Arthur Wesley (Delhi, 1979)
THIS book, of obvious interest to Punjabis the world over, is the result of a happy coincidence. Its author had lived in the Punjab for about a decade and developed deep interest in its his tory and culture. After his return to New Zealand as Professor of History he nostalgically sought the Punjabis settled there. Meanwhile, the authori ties of Guru Nanak Dev University thought of promoting studies concer ned with the life of Punjabis settled abroad. Dr McLeod's project appea red to harmonize with that aspiration. His own association with the University induced him to send the manuscript to us.